2008
DOI: 10.1084/jem.20081915
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Artemis in nonhomologous end-joining during immunoglobulin class switch recombination

Abstract: DNA double-strand breaks (DSBs) introduced in the switch (S) regions are intermediates during immunoglobulin class switch recombination (CSR). These breaks are subsequently recognized, processed, and joined, leading to recombination of the two S regions. Nonhomologous end-joining (NHEJ) is believed to be the principle mechanism involved in DSB repair during CSR. One important component in NHEJ, Artemis, has however been considered to be dispensable for effi cient CSR. In this study, we have characterized the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 42 publications
7
70
2
Order By: Relevance
“…30,31 Previously described Artemis-deficient patients showed a strong dependence on long microhomologies and a complete lack of 'direct end-joining'. 23 The average length of microhomology, defined as successive nucleotides that were shared by both the Sm and Sa regions at the CSR junctions, was not significantly different from control in patient 1 (3.8 ± 5.2 bp versus 1.8±3.2 bp in controls) and in patient 2 (2.0±2.7 bp versus 1.8 ± 3.2 bp in controls). Furthermore, the pattern of Sm-Sa junctions was indistinguishable from that in controls (Table 4).…”
Section: Effect Of the Artemis Mutations On Csrmentioning
confidence: 73%
See 3 more Smart Citations
“…30,31 Previously described Artemis-deficient patients showed a strong dependence on long microhomologies and a complete lack of 'direct end-joining'. 23 The average length of microhomology, defined as successive nucleotides that were shared by both the Sm and Sa regions at the CSR junctions, was not significantly different from control in patient 1 (3.8 ± 5.2 bp versus 1.8±3.2 bp in controls) and in patient 2 (2.0±2.7 bp versus 1.8 ± 3.2 bp in controls). Furthermore, the pattern of Sm-Sa junctions was indistinguishable from that in controls (Table 4).…”
Section: Effect Of the Artemis Mutations On Csrmentioning
confidence: 73%
“…In mature B cells, Artemis is involved in CSR. 23,38 Artemisdeficiency results in CSR characterized by strong dependence of long microhomologies in the S junctions and a complete lack of ''direct end-joining''. We showed that reduced levels of WT Artemis and residual Artemis activity resulted in normal S-junction formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the role of the DNA–PK complex in CSR was considered to be in regulating end processing, possibly by phosphorylating other proteins 25. However, it has since been shown that Artemis is indeed involved in CSR, where its nuclease activity may function in resolving more complex lesions that are generated during CSR 26. The polymerases involved in CSR are thought to include the error prone polymerases, polymerase η and REV1 27, 28…”
Section: Mechanisms Of Recombination In Lymphoid Cellsmentioning
confidence: 99%